HUBUNGAN ANTARA KEMAMPUAN MENYIMAK DAN PRESTASI BELAJAR SISWA SEKOLAH DASAR - Saslia, Imelda Indra Prasetya (Jurnal Sultra Elementary School, 2023)
Listening ability is one of the basic skills that is very important in learning in elementary school. This skill contributes significantly to students' academic success. This article aims to review various literatures related to the relationship between listening ability and elementary school students' learning achievement. This study identified that good listening ability is positively correlated with increased learning achievement, especially in subjects that require verbal comprehension and oral instructions..